2020
DOI: 10.1177/0846537119885666
|View full text |Cite
|
Sign up to set email alerts
|

Value of Apparent Diffusion Coefficient for Assessing Preoperative T Staging of Low Rectal Cancer and Whether This Is Correlated With Ki-67 Expression

Abstract: Purpose: To explore the value of the apparent diffusion coefficient (ADC) in assessing preoperative T staging of low rectal cancer and the correlation between ADC value and Ki-67 expression. Methods: Data on 77 patients with a proven pathology of low rectal cancer were retrospectively analyzed. All patients underwent a magnetic resonance imaging scan 1 week prior to operation, and the mean ADC value was measured. All tumors were fully removed, and pathologic staging was determined. The Ki-67 expression was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
4
15
0
Order By: Relevance
“…DWI also reflects different histopathological features in RC. In the study of Ao et al, ADC correlated well with Ki-67 (r = −0.71, p < 0.01) [ 33 ]. Meng et al showed that ADC correlated with expression of VEGF and HIF 1a [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…DWI also reflects different histopathological features in RC. In the study of Ao et al, ADC correlated well with Ki-67 (r = −0.71, p < 0.01) [ 33 ]. Meng et al showed that ADC correlated with expression of VEGF and HIF 1a [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between different tumor stages and ADC values were reported in 6 studies (352 patients) [14,40,[43][44][45][46]. There were 29 patients (8.2%) with T1 stage, 141 patients (40.1%) with T2 stage, 145 patients (41.2%) with T3 stage, and 37 patients (10.5%) with T4 stage.…”
Section: Adc Values and T Stagementioning
confidence: 99%
“…Figure 5b shows the graphical distribution of ADC values in N0 and N+ tumors. Ao 2020 [14] Peng 2018 [40] Sun 2014 [43] Tang 2018 [45] Xia 2018 [46] Subtotal (95% CI)…”
Section: Adc Values and N Stagementioning
confidence: 99%
See 2 more Smart Citations